Profil alumni FMIPA dan FKIP Universitas Sriwijaya ditinjau dari variabel dan persepsi pada pekerjaan - Irmeilyana Irmeilyana; Endang Sri Kresnawati; Ali Amran; Danny Matthew Saputra (Universitas PGRI Semarang, 2021)
One of the aims of the tracer study is to obtain information about the early careers of alumni, so that some of the questions on the questionnaire need to be explored further. The question items discussed were length of study, length of time to get the first job, field of work, total income, alumni's perception of the closeness of the field of study to work, and the suitability of education level on the job, and taking into account gender and average level of competence. The purpose of this study was to analyze the relationship between these variables in the 2020 tracer study data from alumni of 4 science fields at FMIPA and FKIP Unsri. The method used is descriptive statistics and simple correspondence analysis. Almost all respondents from both faculties stated that the suitability of the level of education with the field of work was at the same level. In respondents from both faculties, there is a significant relationship between respondents' perceptions of the closeness of their field of study with their field of work. The average total income of FMIPA respondents is higher than that of FKIP respondents. FMIPA respondents who stated that their field of study was